Cacao crop management zones determination based on soil properties and crop yield - Carvalho, Perla Silva Matos de; Franco, Laís Barreto; Silva, Samuel de Assis; Sodré, George Andrade; Queiroz, Daniel Marçal de; Lima, Julião Soares de Souza (Revista Brasileira de Ciência do Solo, 2016)
The use of management zones has ensured yield success for numerous agricultural crops. In spite of this potential, studies applying precision agricultural techniques to cacao plantations are scarce or almost nonexistent. The aim of the present study was to delineate management zones for cacao crop, create maps combining soil physical properties and cacao tree yield, and identify what combinations best fit within the soil chemical properties. The study was conducted in 2014 on a cacao plantation in a Nitossolo Háplico Eutrófico (Rhodic Paleudult) in Bahia, Brazil. Soil samples were collected in a regular sampling grid with 120 sampling points in the 0.00-0.20 m soil layer, and pH(H2O), P, K+, Ca2+, Mg2+, Na+, H+Al, Fe, Zn, Cu, Mn, SB, V, TOC, effective CEC, CEC at pH 7.0, coarse sand, fine sand, clay, and silt were determined. Yield was measured in all the 120 points every month and stratified into annual, harvest, and early-harvest cacao yields. Data were subjected to geostatistical analysis, followed by ordinary kriging interpolation. The management zones were defined through a Fuzzy K-Means algorithm for combinations between soil physical properties and cacao tree yield. Concordance analysis was carried out between the delineated zones and soil chemical properties using Kappa coefficients. The zones that best classified the soil chemical properties were defined from the early-harvest cacao yield map associated with the clay or sand fractions. Silt content proved to be an inadequate variable for defining management zones for cacao production. The delineated management zones described the spatial variability of the soil chemical properties, and are therefore important for site-specific management in the cacao crop.
Keywords: Precision agriculture; Unsupervised classification; Soil fertility